2015
DOI: 10.15644/asc49/1/4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Translucency Parameter of Glass-Ceramics Fabricated by Different Techniques

Abstract: Different types of glass-ceramics showed significant difference in TP values both with respect to the fabrication technique and colour. Exposure to a corrosive medium did not result in a statistically significant change of TP values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Promjene u vrijednostima TP-a u primjeni cirkonij-oksidne keramike mogu se objasniti pojavnošću monoklinske faze nakon starenja koja dovodi do stvaranja mikropukotina, poput poroziteta u strukturi, i rezultiraju rasapom svjetlosti reducirajući translucenciju (51 -53). Rezultati K. Ledić i suradnika pokazuju da se vrijednosti TP-a staklokeramika proizvedenih različitim tehnikama i u različitoj boji nisu statistički značajno promijenile nakon izlaganja korozivnom mediju (53). Vrijednosti TP-a u ovom istraživanju potvrđuju četvrtu hipotezu, odnosno prisutnost kubične strukture rezultirala je optimiziranom translucencijom u usporedbi s prethodnim generacijama cirkonij-oksidne keramike, što je u skladu s rezultatima istraživanja Camposilvana i suradnika (38).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Promjene u vrijednostima TP-a u primjeni cirkonij-oksidne keramike mogu se objasniti pojavnošću monoklinske faze nakon starenja koja dovodi do stvaranja mikropukotina, poput poroziteta u strukturi, i rezultiraju rasapom svjetlosti reducirajući translucenciju (51 -53). Rezultati K. Ledić i suradnika pokazuju da se vrijednosti TP-a staklokeramika proizvedenih različitim tehnikama i u različitoj boji nisu statistički značajno promijenile nakon izlaganja korozivnom mediju (53). Vrijednosti TP-a u ovom istraživanju potvrđuju četvrtu hipotezu, odnosno prisutnost kubične strukture rezultirala je optimiziranom translucencijom u usporedbi s prethodnim generacijama cirkonij-oksidne keramike, što je u skladu s rezultatima istraživanja Camposilvana i suradnika (38).…”
Section: Discussionunclassified
“…Two other zirconia ceramics, Prettau Anterior and Zpex Smile, manifested a decrease in the TP value after sintering programs (50). The changes in the TP value of zirconia ceramics can be explained with a post-aging manifestation of the monoclinic phase, which leads to a formation of micro-cracks that account for porosity in the structure and result in dispersion, thus reducing translucency (51)(52)(53). The results of a study by Ledić et al demonstrated that the TP values of glass ceramics varying in color and manufactured using different techniques did not change significantly after being immersed in a 4-percent acetic acid for 16 hours at 80°C (53).…”
Section: Raspravamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, (CIE) approved the clinical parameter of (ΔE), where, 0 value, is perfect; 0.5 to 1, is excellent; 1 to 2 is good; 2 to 3.5, is clinically acceptable; and >3.5, is color mismatch). [28] Thus, ΔE values more than 3.5 value is considered clinically unacceptable, 1 0.00 0.00 0.00 0.00 0.00 0.00 0.00 2 0.00 0.00 0.00 0.00 0.00 0.00 0.00 3 0.00 0.00 0.195 * 0.00 0.00 0.008 0.067 * 4 0.00 0.00 0.195 * 0.00 0.00 0.001 0.008 5 0.00 0.00 0.00 0.00 0.00 0.00 0.00 6 0.00 0.00 0.00 0.00 0.00 0.00 0.00 7 0.00 0.00 0.008 0.001 0.00 0.00 * 0.195 8 0.00 0.00 0.067 * 0.008 0.00 0.00 * 0.195 accordingly, the results of this study were within the range from good to clinically accepted.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] The hot-pressing technique has become a common technique to produce glass-ceramic dental restorations, [3] as heat-pressed glass-ceramic restorations have better fitting accuracy, marginal edge quality, low porosity, as well as high mechanical properties when compared to computer aided design/computer aided manufacture (CAD/CAM) milled materials. [4][5][6] Due to the limitations in ingots shades, the heat-pressed glass ceramic restorations may need to undergo additional firing cycles to improve the esthetic outcome, either for glazing, characteristic dying or even surface veneering. The consequent heat treatments of glass ceramic restoration were associated with changes in material mechanical and optical properties, which affect final clinical results.…”
Section: Introductionmentioning
confidence: 99%